2012
DOI: 10.3855/jidc.1817
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and antimicrobial resistance of bacteria isolated from oral and topical medicaments from Hilla, Iraq

Abstract: Introduction: The presence of microorganisms in pharmaceuticals is undesirable because they may cause spoilage of the product and may present an infection hazard to the consumers or patients.  Methodology: A total of 102 samples of oral and topical non-sterile pharmaceutical products were collected at random from different drug houses and pharmacies in Iraq, to investigate the microbial contamination of these products. Bacterial isolates recovered from these medicaments were subjected to susceptibility testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…On the other hand, El-Houssieny et al had recovered E. coli from a syrup (1.1%); one P. aeruginosa isolate (1.1%) was recovered from a capsule was recovered from a syrup [10]. Contrary to the present study, Al-Charrakh reported the isolation of E. coli (5.7%), S. aureus (20.8%), and P. aeruginosa (1.9%) from a range of pharmaceutical products [23].…”
Section: Discussioncontrasting
confidence: 70%
“…On the other hand, El-Houssieny et al had recovered E. coli from a syrup (1.1%); one P. aeruginosa isolate (1.1%) was recovered from a capsule was recovered from a syrup [10]. Contrary to the present study, Al-Charrakh reported the isolation of E. coli (5.7%), S. aureus (20.8%), and P. aeruginosa (1.9%) from a range of pharmaceutical products [23].…”
Section: Discussioncontrasting
confidence: 70%
“…Also, these findings were consistent with those of previous studies, where the majority of microbial contaminants in non-sterile pharmaceuticals are Bacillus spp. (Mwambete,2010 andAl-Charrakh ,2012).…”
Section: Discussionmentioning
confidence: 99%
“…Our results agreed with the study of researchers [30] as they showed that the sensitivity of P. mirabilis bacteria to the antibiotic Imipenem was 97.2%, and the results differed with the study Researchers [31], [32] reported that the resistance rate of isolates of these bacteria to Imipenem was 16.2% -15%, respectively. The reason for the resistance of some bacterial genera and species to many antibiotics, especially the species of the Enterobacter family of Gram-negative bacteria, K. pneumonia, P. mirabilis, and E. coli, is due to several reasons, including the production of enzymes that destroy the beta-lactam ring present in the composition of antibiotics belonging to the group Beta-lactams [33], or their possession of a capsule, or their possession of efflux pumps, or their formation of a biofilm substance that surrounds colonies of bacterial cells, providing them with a type of protection that greatly 2) OFX( 3) CAZ( 4) TE( 5) F( 6) AZM( 7) IPM( 8) CTX( 9) TOB( 10) 4) TE( 5) F( 6) AZM( 7) IPM( 8) CTX( 9) TOB (10) hinders and prevents antibiotics from reaching the bacterial cell [34], and that the excessive use of antibiotics has led to an increasing rate of the development of resistance to them and its spread throughout the world, and that when bacteria coexisting in the human and animal bodies are exposed to antibiotics, they will also develop resistance to these antibiotics, and worse than that, bacteria that are resistant to antibiotics It can spread to other people and the environment [35], [36].…”
Section: Testing the Sensitivity Of Gram-negative And Positive Bacter...mentioning
confidence: 99%